A Multi-Pronged Approach to Control Healthcare Facility-Onset Clostridium difficile Infection in a Tertiary Care Community Hospital. (4th October 2017) - Chinn, Raymond; Wyatt, Jennifer; Wells, Pam; Fox, Tracy; Daley, Jacqueline; Willon, Judy; Magdaluyo, Patty; Mabalot, Shannon; Kramer, Janie; Tarrac, Shauna; Vasina, Logan; Angus, Gene; et al.
Abstract: Background: Clostridium difficile infection (CDI) contributes to significant increases in healthcare-associated morbidity and mortality. Multiple strategies have been promulgated to accurately diagnose and to control healthcare facility-onset (HO) CDI. Sharp Memorial Hospital is a 438-bed tertiary care community hospital. In 2014, the standardized infection ratio (SIR) CDI was 1.406 (2006–2008 baseline) with a p value of 0.0005. We report the results of a multi-disciplinary approach that has reduced our HO-CDI SIR. The National Healthcare Safety Network definitions and methodologies were used throughout the study. Methods: Various multi-disciplinary interventions were implemented over a 12 month period from April 2015 through March 2016 that included enhanced administrative support and the creation of a multi-disciplinary CDI Steering Committee (Figure 1). A Lean Six Sigma approach was launched that included a two-day rapid process improvement (RPI) workshop in July 2015 with participation of an interdisciplinary team of frontline staff, leaders from the 2 units with high CDIs, Infection Prevention, and Environmental Services. Subsequently, lessons learned from the RPI were disseminated throughout the hospital. The laboratory and information technology staff and the antimicrobial stewardship program also contributed. Results: Compared with the intervention period, the post intervention period (April 2016 through March 2017) documented a significant increase in the number of samples submitted for CDI testing ≤ 3 days after admission and a significant decrease in the number of samples submitted > 3 days after admission. There were significant decreases in the HO-CDI SIR from 0.947 to 0.676 (p value 0.0485) and in quinolone days of therapy from 265 to 246 (p value 0.0001). Conclusion: We have demonstrated a significant decrease in our HO-CDI using a multi-pronged approach that highlighted a return and reinforcement of back to basics infection prevention. High HO-CDI SIR in previous years might indicate missed community-onset, community-onset healthcare facility-associated cases. We did not employ other technologies such as the hands-free disinfection devices. Sustainability remains a future challenge. Disclosures: All authors: No reported disclosures.